1997
DOI: 10.1007/s002329900236
|View full text |Cite
|
Sign up to set email alerts
|

On the Role of Calcium in the Regulatory Volume Decrease (RVD) Response in Ehrlich Mouse Ascites Tumor Cells

Abstract: The putative role for Ca2+ entry and Ca2+ mobilization in the activation of the regulatory volume decrease (RVD) response has been assessed in Ehrlich cells. Following hypotonic exposure (50% osmolarity) there is: (i) no increase in cellular Ins(1,4,5)P3 content, as measured in extracts from [2-3H]myoinositol-labeled cells, a finding at variance with earlier reports from our group; (ii) no evidence of Ca2+-signaling recorded in a suspension of fura-2-loaded cells; (iii) Ca2+-signaling in only about 6% of the s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
41
2

Year Published

1997
1997
2003
2003

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 67 publications
(51 citation statements)
references
References 45 publications
8
41
2
Order By: Relevance
“…In hyposmotic medium, these [Ca 2+ ]i responses were not reflected in dramatic changes of the mean [Ca 2+ ]i levels but were clearly visible at the individual cell level. The reason underlying the heterogeneity of cellular responses is not clear, but a remarkable variability at the cell level has also been reported for other cells (Jorgensen et al, 1997). As in this previous study, the alterations of [Ca 2+ ]i did not seem to be closely related to the changes of cell volume in the trout hepatocytes.…”
Section: Cell Volume and [Ca 2+ ]Icontrasting
confidence: 42%
“…In hyposmotic medium, these [Ca 2+ ]i responses were not reflected in dramatic changes of the mean [Ca 2+ ]i levels but were clearly visible at the individual cell level. The reason underlying the heterogeneity of cellular responses is not clear, but a remarkable variability at the cell level has also been reported for other cells (Jorgensen et al, 1997). As in this previous study, the alterations of [Ca 2+ ]i did not seem to be closely related to the changes of cell volume in the trout hepatocytes.…”
Section: Cell Volume and [Ca 2+ ]Icontrasting
confidence: 42%
“…In both cell types it was demonstrated that RVD proceeds without increase, or even during a decrease, in [Ca 2ϩ ] i . RVD was not affected by maneuvers preventing Ca 2ϩ influx or its intracellular release (9,37). Cell swelling-and membrane stretch-activated K ϩ channels have been reported in gall bladder epithelium (38).…”
Section: Rvd Acceleration In Mtask-2-expressing Hek-293 Cells-mentioning
confidence: 83%
“…As described by others (Jorgensen et al, 1997;Wang et al, 1996), a percent volume recovery at X minutes after hypotonic exposure was calculated as [(Vmax-VX min)/(Vmax-V0)]×100, where Vmax is the peak relative cell volume, V0 is the initial relative volume (or one) and VX min is the relative cell volume measured X minutes after hypotonic exposure. A percent volume decrease was calculated as [(percent recoveryexperimental)/ (percent recoverycontrol)]×100, where maximal recovery in hypotonic Ringer is 100%.…”
Section: Coulter Countermentioning
confidence: 99%